Determination of Antimicrobial Resistance Patterns in Salmonella from Commercial Poultry as Influenced by Microbiological Culture and Antimicrobial Susceptibility Testing Methods - Xi Wang; W. Evan Chaney; Hilary O. Pavlidis; James P. McGinnis; J. Allen Byrd; Yuhua Z. Farnell; Timothy J. Johnson; Audrey P. McElroy; Morgan B. Farnell (Microorganisms, 2021)
Monitoring antimicrobial resistance of foodborne pathogens in poultry is critical for food safety. We aimed to compare antimicrobial resistance phenotypes in Salmonella isolated from poultry samples as influenced by isolation and antimicrobial susceptibility testing methods. Salmonella isolates were cultured from a convenience sample of commercial broiler ceca with and without selective broth enrichment, and resistance phenotypes were determined for 14 antimicrobials using the Sensititre® platform and a qualitative broth breakpoint assay. The broth breakpoint method reported higher resistance to chloramphenicol, sulfisoxazole, and the combination of trimethoprim and sulfamethoxazole, and lower resistance to streptomycin as compared to the Sensititre® assay in trial one. Selective enrichment of samples containing Salmonella in Rappaport-Vassiliadis broth reported lowered detectable resistance to amoxicillin/clavulanic acid, ampicillin, azithromycin, cefoxitin, ceftriaxone, nalidixic acid, and meropenem, and increased resistance to streptomycin and tetracycline than direct-plating samples in trial one. Using matched isolates in trial two, the Sensititre® assay reported higher resistance to chloramphenicol and gentamicin, and lower resistance to nalidixic acid as compared to the broth breakpoint method. These results suggest methodology is a critical consideration in the detection and surveillance of antimicrobial resistance phenotypes in Salmonella isolates from poultry samples and could affect the accuracy of population or industry surveillance insights and intervention strategies.